Photoluminescence characteristics of GaInNAs quantum wells annealed at high temperature - Ng, T. K. (2013)
The photoluminescence (PL) characteristics of GaInNAs quantum wells (QWs) after high-temperature postgrowth annealing were studied. The QWs were grown using a radio-frequency nitrogen plasma source in conjunction with a solid-source molecular-beam epitaxy system. It was found that annealing at high temperature (840 °C) and long duration (10min) results in significant improvements to the PL characteristics of the GaInNAs QWs. The shift of the GaInNAs and GaInAs PL peak wavelength resulting from high-temperature annealing is dependent on the In composition. It is suggested that the dominant mechanisms that give rise to the blueshift of the PL peak wavelength in GaInNAs QWs with high-In composition are residual-strain-induced GaAs/ GaInNAs/GaAs interface interdiffusion, and defect-assisted diffusion-related effects, both of which originate from the growth process.